2020
DOI: 10.1186/s12888-020-02988-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of traumatic events with levels of psychological distress and depressive symptoms in male asylum seekers and refugees resettled in Italy

Abstract: Background In recent years there has been a progressive rise in the number of asylum seekers and refugees displaced from their country of origin, with significant social, economic, public health and mental health implications. The aim of this study is to (1) describe the level of psychological distress and frequency of psychiatric disorders in a sample of male asylum seekers and refugees across different ethnic groups resettled in Italy; (2) establish whether the number of traumatic events experienced before, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Similarly, staying in a low-income (39•29 [11•96-129•70]) or middle-income country (8•09 [CI 3•06-21 •40]) was associated with an increased prevalence of current generalised anxiety disorder when compared with migrants residing in high-income countries (table 2). Furthermore, a younger age was associated with a higher Post-traumatic stress disorder Gülşen et al (2010) 37 Salah et al (2013) 49 Bogic et al (2012) 32 Alejo et al (2007) 28 Tekeli-Yesil et al (2018) 56 Kazour et al (2017) 40 Bapolisi et al (2020) 29 Al Ibraheem et al (2017) 27 Tekin et al (2016) 57 Kaur et al (2020) 39 Caroppo et al (2020) 34 Kira et al (2017) 41 Turner et al ( 2003) 58 Botelho de Oliveira et al (2011) 33 Momartin et al ( 2004) 45 Nosè et al (2020) 47 Söndergaard et al ( 2001) 53 Bhui et al ( 2006) 31 Roth et al ( 2006) 48 Llosa et al (2014) 43 Civan Kahve et al (2021) 35 Sundvall et al (2020) 55 Widmann 49 Bogic et al (2012) 32 Tekeli-Yesil et al (2018) 55 Bapolisi et al (2020) 29 Naja et al (2016) 46 Tekin et al (2016) 57 Kaur et al (2020) 39 Sheikh et al (2015) 51 Bhui et al ( 2006) 31 Llosa et al (2014) 43 Nosè et al (2020) 47 Caroppo et al (2020)…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, staying in a low-income (39•29 [11•96-129•70]) or middle-income country (8•09 [CI 3•06-21 •40]) was associated with an increased prevalence of current generalised anxiety disorder when compared with migrants residing in high-income countries (table 2). Furthermore, a younger age was associated with a higher Post-traumatic stress disorder Gülşen et al (2010) 37 Salah et al (2013) 49 Bogic et al (2012) 32 Alejo et al (2007) 28 Tekeli-Yesil et al (2018) 56 Kazour et al (2017) 40 Bapolisi et al (2020) 29 Al Ibraheem et al (2017) 27 Tekin et al (2016) 57 Kaur et al (2020) 39 Caroppo et al (2020) 34 Kira et al (2017) 41 Turner et al ( 2003) 58 Botelho de Oliveira et al (2011) 33 Momartin et al ( 2004) 45 Nosè et al (2020) 47 Söndergaard et al ( 2001) 53 Bhui et al ( 2006) 31 Roth et al ( 2006) 48 Llosa et al (2014) 43 Civan Kahve et al (2021) 35 Sundvall et al (2020) 55 Widmann 49 Bogic et al (2012) 32 Tekeli-Yesil et al (2018) 55 Bapolisi et al (2020) 29 Naja et al (2016) 46 Tekin et al (2016) 57 Kaur et al (2020) 39 Sheikh et al (2015) 51 Bhui et al ( 2006) 31 Llosa et al (2014) 43 Nosè et al (2020) 47 Caroppo et al (2020)…”
Section: Resultsmentioning
confidence: 99%
“…In case of acute mental disorders with agitation, de-escalation techniques aimed at avoiding coercive measures can be unfeasible thus less effective with immigrants, especially refugees and asylum seekers (Tarsitani et al, 2013). Post-traumatic symptoms have recently been highlighted as very frequent in asylum-seekers and refugees (Nosè et al, 2020). These symptoms could influence the doctor-patient relationship to the extent that the hospital environment could in itself trigger retraumatization (Schock et al, 2016), leading to activation and therefore reducing the possibility of a shared choice with the doctor.…”
Section: Discussionmentioning
confidence: 99%
“…Migration has been shown to be a risk factor for the development of a variety of mental disorders, including psychotic disorders and major mood disorders (Cantor-Graae & Pedersen, 2013; Cantor-Graae & Selten, 2005; Swinnen & Selten, 2007; Turrini et al, 2017). First-generation forced migrants are frequently exposed to severe traumatic events (Miller & Rasmussen, 2010; Nosè et al, 2020) and they are at higher risk of being diagnosed with mental disorders than economic immigrants (Brandt et al, 2019; Tarsitani & Biondi, 2016; Turrini et al, 2017). Nevertheless, immigrants have difficulty to access community mental health care in high-income countries (Kiselev et al, 2020a, 2020b; Nosè et al, 2014; Satinsky et al, 2019) possibly leading to a delayed treatment that may worsen the disease course (Ghio et al, 2014; Marshall et al, 2005) and increase the risk of emergency referrals.…”
Section: Introductionmentioning
confidence: 99%
“…PTS rates among Bhutanese refugees in the United States are high, ranging between 4.5% and 6.2% (Adhikari et al, 2015; Ao et al, 2012); reported severe PTS include trouble sleeping, difficulty concentrating, and recurring nightmares (Adhikari et al, 2015). PD is found to be associated with PTS in a Swedish study among mixed refugees (Nosè et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%